Diversity of Arbuscular Mycorrhizal Fungi (AMF) in Rhizosphere of Some Economic and Medicinal Crops in SEAMEO BIOTROP, Bogor, West Java - Henokh Christian Prasgi; Risa Rosita; Rizky Susanti; Ayu Paraswati Kusuma Dewi; Fransiscus Jason Wiguna; Novita Dwi Yanti; Sunardi Ikay; Lusiawati Dewi (Journal of Science and Science Education, 2022)
The diversity of terrestrial plants in Indonesia are very huge, including production crops such as palm oil (Elaeis sp.), teak (Tectona grandis L.), lemon (Citrus limon L.) and Aloe vera. The quality of production crops is influenced by the diversity of soil microorganisms, namely the Arbuscular Mycorrhizal Fungi (AMF). AMF plays an important role in the growth and development of the host plant. This study aims to determine the diversity of AMF in the rhizosphere of some production crops at SEAMEO BIOTROP, West Java. Research methods are soil sampling and preparation, soil sieving, AMF spore extraction and morphological identification. As a result, spore density tends to be uniform in all four plants (3 spores per 10 gram). The highest to lowest relative abundance percentage of spores on Glomus sp. (52.17%), Acaulospora sp. (34.79%) and Gigaspora sp. (13,04%). Soil, host plant and AMF factors affect the diversity of AMF.